Journalistic Criminalization: “The Dialectic between Legal Text and Practical Application in the Press Law of the Kurdistan Region of Iraq” - Omar, Djwar; Ibrahim, Taghreed (Journal of Legal Sciences, 2026)
This research examines the legislative shortcomings of the Kurdistan Region Journalism Law No. 35 of 2007, highlighting the gap between traditional legal texts and the challenges of contemporary digital media. The core problem lies in the lack of precise legal classification for journalistic genres (news, opinion, and visual media), leading to inconsistencies in determining criminal liability and legal characterization of offenses. Using a critical analytical approach, the study explores the philosophy of criminalization and the balance between freedom of expression and legal accountability. It concludes that professional ethical codes must serve as the fundamental basis for reforming legislation to align with technological advancements and safeguard the public interest.